Evaluation Course Master of Midwifery Education Based on CIPP Model (CIPP) in Ardabil School of Nursing and Midwifery - Shiva Jegargoosheh; Amirhosein Maghari; aziz Kamran (Babol University of Medical Sciences, 2022)
Background and Objective: Evaluation is an indicator that shows the extent to which educational goals have been achieved and analyzes educational activities. For this purpose, this study was conducted with the aim of evaluating the "period" of the master's degree in midwifery education based on the CIPP evaluation model in Ardabil School of Nursing and Midwifery. Methods: The present study was performed cross-sectionally in 1400. The target population was faculty members and postgraduate students in the Department of Midwifery Education of Ardabil University of Medical Sciences, including 11 professors and 7 students. All samples participated in this study by census method. To collect information, a researcher-made questionnaire was used to evaluate the master's course in midwifery education based on the CIPP evaluation model for professors and students. One-Sample T-Test was used for data analysis. Statistical analysis was performed by SPSS software version 21. The level of statistical significance in this study was considered 0.05. Findings: The mean obtained in the group of students and professors in the scope of field (18.29 ± 3.04 and 31.45 ± 2.81), input (47.29 ± 1.70 and 51.18 ± 3.52), process (10.43 ± 0.98 and 40.55 ± 1.92) and in the output area (9.43 ±1.40 and 29.27 ±2.37) that the scores in the group of students in 4 areas are less than the standard score and in the group Professors were higher than the standard score. Conclusion: The results showed that the evaluation of the master's degree in midwifery education at Ardabil School of Nursing and Midwifery was unfavorable for students and desirable for professors. Therefore, in order to promote this field, cooperation between experts in this field and planners is necessary in order to solve the problems.